2016
DOI: 10.17129/botsci.284
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation patch dynamics and tree diversity in a diverse conifer and oak forest in central Mexico

Abstract: Mexican conifer and oak forests are very diverse, and represent the vegetation type with the highest timber production in Mexico. Yet, there is little knowledge about the relationship of forest recovery and tree diversity in this type of vegetation. In this study, we analyzed the dynamics of vegetation patches over three time periods covering five decades, within an area in central Mexico dominated by conifer and oak forest. We identified vegetation patches, and evaluated their number and changes in patch size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 28 publications
3
14
0
9
Order By: Relevance
“…During the study period, we found scats of gray fox, coyote, ringtail, coati, and bobcat, which are associated with seed dispersal in the temperate and the tropical dry forest, while plants dispersed -Núñez et al, 2016). This is the case for A. pungens, the seeds of which were dispersed at a higher average abundance in the scats of gray fox, which corroborate previous findings for the same species (e.g., Rubalcava-Castillo et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…During the study period, we found scats of gray fox, coyote, ringtail, coati, and bobcat, which are associated with seed dispersal in the temperate and the tropical dry forest, while plants dispersed -Núñez et al, 2016). This is the case for A. pungens, the seeds of which were dispersed at a higher average abundance in the scats of gray fox, which corroborate previous findings for the same species (e.g., Rubalcava-Castillo et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…), oak (Quercus potosina), Chihuahua pine or ocote chino (Pinus leiophylla var. Chihuahuana), and twisted leaf pine or pino colorado (Pinus teocote), among others (Díaz-Núñez et al, 2016). On the other hand, the tropical dry forest has an average annual precipitation of 625 mm (Sosa-Ramírez, 1998), and the plant communities are composed of blue myrtle-cactus (Myrtillocactus geometrizans), palo bobo (Ipomea murucoides), kidneywood tree (Eysenhardthya polystachya), torchwood copal (Bursera fagaroides), and palo blanco (Forestiera phillyreoides), among others (Argumedo-Espinoza et al, 2018).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…These two plateaus are separated by the ravine Cañada de Piletas . Based on pre‐existing maps of the vegetation cover by Díaz‐Núñez et al (), where, for the estimation of forest coverage, a SPOT ® 2013 satellite image of 5 meters resolution was used. The study area was divided into patches or fragments that form continuous mosaics within a landscape and four categories of coverage were established for the landscape classification: 1 = ≤10%, 2 = 11%–30%, 3 = 31%–50%, and 4 ≥50%.…”
Section: Methodsmentioning
confidence: 99%
“…In Aguascalientes, Mexico, the Área Natural Protegida Sierra Fría (the Sierra Fría Protected Natural Area or ANP‐SF by its Spanish acronym) includes a group of ecosystems belonging to three biogeographic provinces (Sosa Ramírez, Breceda‐Solís, Jiménez‐Sierra, Iñiguez‐Dávalos, & Ortega‐Rubio, ). Díaz‐Núñez, Sosa‐Ramírez, and Pérez‐Salicrup () describe the recovery of these ecosystems since the 1990s, reporting that the pioneer species that present the greatest distribution and colonization of the area postdisturbance are the pointleaf manzanita or pingüica ( Arctostaphylos pungens Kunth; Ericaceae), which is a fire‐adapted plant that thrives in places where events have frequently destroyed holm oak trees (Rzedowski, ), and the checkerbark juniper or táscate ( Juniperus deppeana Steud; Cupressaceae), which is a dioecious species that lives in temperate to semiarid environments and is tolerant to alkaline and nutrient poor soils (Batis, Alcocer, Gual, Sánchez, & Vázquez‐Yánez., C., ; Martínez, ). Both of these plant species act as nurse species to other larger species.…”
Section: Introductionmentioning
confidence: 99%